2021
DOI: 10.3390/app11209589
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fracture Strengths of Three Provisional Prosthodontic CAD/CAM Materials: Laboratory Fatigue Tests

Abstract: Temporary restorations play a fundamental role in oral rehabilitation. They can be used on teeth or implants for a variable period of time during the period prior to rehabilitation with definitive restorations. Temporary or provisional restorations manufactured via CAD/CAM methods are becoming increasingly used in the intermediate phase of the treatment of complex cases. The main objective of this study was to compare the fracture resistance of three materials used in the creation of provisional crowns on impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The biocompatible high-performance polymer polyether ether ketone (PEEK) that was analyzed in the present study has been used in dentistry for dental implants [18][19][20] as well as for permanent and removable dentures [14,15]. In the orthodontic field, PEEK has been tested for the manufacturing of removable and fixed space maintainers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biocompatible high-performance polymer polyether ether ketone (PEEK) that was analyzed in the present study has been used in dentistry for dental implants [18][19][20] as well as for permanent and removable dentures [14,15]. In the orthodontic field, PEEK has been tested for the manufacturing of removable and fixed space maintainers.…”
Section: Discussionmentioning
confidence: 99%
“…The material can be milled and is-with some limitations-also 3D printable [16,17]. Due to its excellent biocompatibility, PEEK was also chosen for dental implants as well as for removable and fixed dentures [18][19][20]. With its small Young's modulus of 3-5 GPa, PEEK may also be a good candidate for metalfree, aesthetic orthodontic appliances.…”
Section: Introductionmentioning
confidence: 99%
“…The provisional restoration can be manufactured using a silicone matrix or a vacuum on a preoperative cast or on an ideally contoured waxing of the replacement tooth [ 4 ]. A properly adapted ISPR implies better esthetics, contouring and architectural modeling of the upper peri-implant tissue [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the deleterious effects of weak intraoral acids (citric and lactic acid) on inorganic fillers can also contribute to a decrease in materials’ hardness [ 13 , 19 ]. Thus, fracture resistance is very relevant and should be considered when choosing material for temporary restorations [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dokania, R. et al suggested the term “guided tissue healing” to describe the use of a provisional restoration for guiding soft-tissue architecture. This is a state-of-the-art approach in implantology [ 1 , 2 ], which also allows for rehabilitation during the period of osseointegration, as well as restores the function, phonetics, esthetics, and adaptation to the final shape of the restoration. The temporary restoration plays a fundamental role in oral rehabilitation [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%